#### Answer

$f'(w) = 2w$

#### Work Step by Step

Quotient Rule:
$f(w) = \frac{w^3-w}{w}$
$f'(w) = \frac{(3w^2-1)(w)-(w^3-w)(1)}{w^2} = 2w$
Division Then Power Rule:
$f(w) = \frac{w^3-w}{w} = w^2-1$
$f'(w) = 1(2)w^{2-1}-1(0)w^{0-1} = 2w$

Published by
Pearson

ISBN 10:
0321947347

ISBN 13:
978-0-32194-734-5

$f'(w) = 2w$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.